Birth Weight is not Associated With Risk of Fracture: Results from Two Swedish Cohort Studies. (October 2014) - Byberg, Liisa; Michaëlsson, Karl; Goodman, Anna; Zethelius, Björn; Koupil, Ilona
Abstract Development and growth in utero has been suggested to influence bone health. However, the relationship with risk of fracture in old age is largely unknown. Using Cox proportional hazards regression, we studied the association between birth weight and fractures at ages 50–94 among 10, 893 men and women (48% women) from the Uppsala Birth Cohort Study (UBCoS, born 1915–29) and 1334 men from the Uppsala Longitudinal Study of Adult Men (ULSAM, born 1920–24). Measured birth weight was collected from hospital or midwives' records and fractures from the Swedish National Patient Register. We observed 2796 fractures (717 of these were hip fractures) in UBCoS and 335 fractures (102 hip fractures) in ULSAM. In UBCoS, the hazard ratio (HR) per 1 kg increase in birth weight, adjusted for sex and socioeconomic status at birth, was 1.01 [95% confidence interval (CI), 0.94–1.09] for any fracture and 1.06 (95% CI, 0.91–1.23) for hip fracture. Estimates in ULSAM were similar. We did not observe a differential association of birth weight with fractures occurring before age 70 or after age 70 years. Neither birth weight standardized for gestational age nor gestational duration was associated with fracture rate. In linear regression, birth weight was not associated with bone mineral density among 303 men who were 82‐years‐old in ULSAM but showed positive associations with total body bone mineral content (β per kg increase in birth weight, adjusted for social class and age, 133; 95% CI, 30–227). This association was attenuated after further adjustment for body mass index and height (β, 41; 95% CI, ‐43–126). We conclude that birth weight is associated with bone mineral content but this association does not translate into an association with risk of fracture in men and women aged 50–94 years. © 2014 American Society for Bone and Mineral Research.